OPTIMIZATION OF ORTHOPEDIC TREATMENT OF DENTAL DEFECTS IN PATIENTS WITH CHRONIC GASTROINTESTINAL DISEASES (Spectrum Journal of Innovation, Reforms and Development, 2022)
Prosthetics for defects in teeth and dentition is one of the most important links in specialized medical care for the population. Prosthetics - not only eliminates the aesthetic defect, restores the impaired function of the dentition, but also serves as an important way to prevent diseases of the gastrointestinal tract.